FRIEND RELATIONSHIP WEIGHTING FOR ACADEMIC PERFORMANCE PREDICTION ON UNIVERSITY DELEGATION AT FOLLOWING COMPETITION - Bisono, Eva Firdayanti; Fahrudin, Tora; Buliali, Joko Lianto (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2019)
Academic performance is an important key to student success or failure. Therefore, academic performance prediction become a popular research on education. In general, several researches used GPA to predicting academic performance. However, there are some aspect that also plays a role in student academic performance, like friend relationship. So, this paper will analyze the correlation between academic performance and friend relationship. Friendship will be seen from communication frequency between students when become University delegation. Each students friend will have weight to show their closeness. In this paper, proposed method gives friendship weight based on communication frequency proportion between student among all student in one faculty. Indeed, close friends have a higher weight than other friends. So, the friendship weight sorted into descending order to get the closest friend. Then, their GPA convert into academic label, i.e. cumlaude, excellent, very good, or drop out. Furthermore, label will be compared to obtaining validation of our hypotheses that friendship plays a role in academic performance achievement. We use scholar student delegation dataset in competition from year 2015 in 7 study programme with 160 scholar students. Experimental results showed that the proposed method can predict academic performance 43% from the total data sample.